Influence of alkali metal formates and calcium formate on workability, hydration and basic properties of reactive powder concrete - Kratochvílová, Nikola; Šoukal, František; Novotný, Radoslav; Sedlačík, Martin; Švec, Jiří; Másilko, Jiří; Ptáček, Petr; Bocian, Luboš; Hajzler, Jan; Marko, Michal (Springer Nature, 2024)
This work aims to study whether it would be possible to use alkali metal formates and calcium formate in order to increase the workability of reactive powder concrete (RPC) and how these additives affect hydration, mechanical properties and mineralogical composition of RPC. These substances were added together with superplasticizer. Therefore, paper deals with possibility of increase in workability which would be higher when compared to the sole addition of only the superplasticizer themself. The effect of alkali metal formates and their replacement with calcium formate on slump flow, mechanical properties and pH of RPC was studied. Furthermore, the influence of potassium formate and its replacement with calcium formate and with calcium oxide on the hydration of RPC was observed with the help of isothermal calorimetry and thermal analysis. The results showed that the addition of studied compounds allows to achieve an increase in RPC slump flow. However, it is necessary to add these substances in an optimal ratio of alkali metal formate/calcium formate because a higher content of calcium formate leads to a decrease in slump flow. For ideal ratios, the compressive strength after 90 days is still above 218 MPa and the flexural strength is still above 23 MPa. In calorimetric measurements, it was observed that the addition of potassium formate leads to a decrease in the total amount of heat developed in the induction period. According to thermal analysis, additions of the studied additives to RPC caused changes in the content of portlandite and calcite.

This work aims to study whether it would be possible to use alkali metal formates and calcium formate in order to increase the workability of reactive powder concrete (RPC) and how these additives affect hydration, mechanical properties and mineralogical composition of RPC. These substances were added together with superplasticizer. Therefore, paper deals with possibility of increase in workability which would be higher when compared to the sole addition of only the superplasticizer themself. The effect of alkali metal formates and their replacement with calcium formate on slump flow, mechanical properties and pH of RPC was studied. Furthermore, the influence of potassium formate and its replacement with calcium formate and with calcium oxide on the hydration of RPC was observed with the help of isothermal calorimetry and thermal analysis. The results showed that the addition of studied compounds allows to achieve an increase in RPC slump flow. However, it is necessary to add these substances in an optimal ratio of alkali metal formate/calcium formate because a higher content of calcium formate leads to a decrease in slump flow. For ideal ratios, the compressive strength after 90 days is still above 218 MPa and the flexural strength is still above 23 MPa. In calorimetric measurements, it was observed that the addition of potassium formate leads to a decrease in the total amount of heat developed in the induction period. According to thermal analysis, additions of the studied additives to RPC caused changes in the content of portlandite and calcite.
Influence of alkali metal formates and calcium formate on workability, hydration and basic properties of reactive powder concrete
Keywords: RPC; Flow; Calorimetry; Mechanical properties; Thermal analysis; pH; RPC; Flow; Calorimetry; Mechanical properties; Thermal analysis; pH